AB0033 The identification of IL-17A+, IL-17RA+ and IL-17RC+ lymphoid and myeloid cells in blood of treatment naÏve early and in synovial fluid of established psoriatic arthritis patients. (15th June 2017) - Xu, X; Davelaar, N; Otten-Mus, A-M; Asmawidjaja, PS; Braanker, H den; Alves, H; Hamburg, JP van; Gaillez, C; Hazes, JM; Bisoendial, R; Vis, M; Kolbinger, F; et al.
Abstract : Background: Interleukin (IL)-17A is a pro-inflammatory cytokine and is involved in the pathogenesis of psoriatic arthritis (PsA) (1, 2). Various cells can produce IL-17A. However, it is not clear which cell types in PsA patients are responsible for the production of IL-17A. In addition, the expression of IL-17RA and IL-17RC on different cell types is not well defined. Objectives: To identify IL-17A, IL-17RA and IL-17RC positive cells in blood of first diagnosed PsA patients with arthritis and in synovial fluid of established PsA patients with active disease. Methods: Fresh blood was taken from first diagnosed DMARD and steroid naïve PsA patients (n=10), having arthritis in 1 or more joints (PsA blood). The diagnosis was made by a rheumatologist according to the CASPAR-criteria. In addition, fresh synovial fluid was obtained from established PsA patients (PsA SF) with active disease (n=10) and treated with either methotrexate (n=3) or adalumimab (n=3) or NSAIDs (n=4). Multicolor flow cytometric analysis was performed on PsA blood and PsA SF. For the detection of IL-17A, IL-17RA or IL-17RC the following antibodies were used: IL-17A-PE (eBioscience), IL-17RA or isotype control IgG1k (both Biolegend), IL-17RC or isotype control IgG2b (both R&D systems). The following markers were used to discriminate between different cell populations: T cell subsets (CD3, CD4, CD8, CD45RO, CCR6, TCRγδ), B cells (CD19), NK cells (CD15-CD16+), neutrophils (CD15+CD16+), monocytes (CD33+CD14+CD16+/-), mast cells (CD117+FcER1a+) and eosinophils (CD15+FcER1a+). Results: Different lymphoid and myeloid cell types were IL-17A positive in PsA blood of first diagnosed PsA patients such as CD3+, TCRγδ+, CD4+, CD8+ lymphoid cells, CD14+ monocytes and eosinophils. In PsA SF of established PsA patients TCRγδ+ T cells, neutrophils, NK cells and eosinophils were IL-17A positive. In both groups, no difference in expression of IL-17RA and IL-17RC was found on CD4+, CD8+, CD4+CD45RO+CCR6+/-, TCRγδ+ and CD19+ lymphoid cells compared to their isotype control. In contrast, the expression of IL-17RA and IL-17RC was increased compared to their isotype control on neutrophils and monocytes in PsA blood and on neutrophils, monocytes, mast cells and eosinophils in PsA SF. Conclusions: These preliminary data show that not only lymphoid cells but also specific myeloid cell types may be sources of IL-17A in PsA. Furthermore, not lymphoid cells but IL-17RA/IL-17RC positive myeloid cells such as monocytes, neutrophils, mast cells and eosinophils may be potential target cells for IL-17A. Together, these data suggest a more broad, but specific IL-17A-IL-17RA/RC signaling network between different cell types important in the IL-17A-driven pathogenesis of PsA. References: Lubberts E. Nat Rev Rheumatol 2015, 11: 415–29. McInnes IB, et al. Lancet 2015, 386: 1137–46. Disclosure of Interest: None declared